Multiple Myeloma Patient Tumors With High Levels of Cereblon Exon-10 Deletion Splice Variant Upregulate Clinically Targetable Pro-Inflammatory Cytokine Pathways - Karagoz, Kubra; Stokes, Matthew; Ortiz-Estévez, María; Towfic, Fadi; Flynt, Erin; Gooding, Sarah; Pierceall, William; Thakurta, Anjan (Frontiers in Genetics, 2022)
Immunomodulatory drugs (IMiDs), including lenalidomide and pomalidomide, are used in the standard treatment for multiple myeloma (MM) patients. Cereblon (CRBN) is the direct molecular target of IMiDs. While not an essential gene for MM cell proliferation, the frequency of CRBN genetic aberrations including mutation, copy number loss and exon 10 (which includes a portion of the IMiD-binding domain) splicing, have been reported to incrementally increase in later-line patients. CRBN exon 10 splicing has also been shown to be associated with decreased progression free survival in both newly diagnosed and relapsed refractory MM patients. Although, we did not find significant general splicing defects among patients with CRBN exon 10-spliced variant when compared to those expressing CRBN full length transcript; we did identify upregulated TNFA signaling via NFKB, inflammatory response, and IL-10 signaling pathways in patients with exon 10-spliced variants across various datasets - all potentially promoting tumor growth as chronic growth signals. Master regulators that mediate transcriptional programs in CRBN exon 10-spliced variants patients were examined identifying BATF, EZH2, and IKZF1 across four datasets. Upregulated targets of BATF, EZH2 and IKZF1 are components of TNFA signaling via NFKB, IL2/STAT5 signaling pathways and IFNG response. Previously, BATF-mediated transcriptional regulation was associated with venetoclax sensitivity in MM. Together, these data provide rationale for investigating EZH2 inhibitors or venetolax in combination with next generation CRBN-targeting agents, such as CELMoDs, for patients expressing the CRBN exon 10-spliced variant.